Marketing Practices and Employability in Traditional Backyard Poultry Rearing in Bastar District of Chhattisgarh, India - Chaturvedani, A. K.; Lal, Niranjan; Dhruw, Kalpana; Jaiswal, S. K. (International Journal of Bio-resource and Stress Management, 2023)
The present study was carried out in the Bastar district of Chhattisgarh with the specific objective to assess the marketing practices and employability related to backyard poultry production of desi birds during February to April, 2014. A total of 120 poultry rearers (12 respondents from each village) were randomly selected from two blocks (Bakawand, Jagdalpur) of Bastar district of Chhattisgarh. The data was collected from the selected poultry rearers through a structured interview schedule after initial pre-testing. The findings of the study revealed 131.01±0.81 man days employment year-1 was generated through backyard poultry rearing to the total family members. The employment was highest for adult female members (69.10±0.99 man days year-1), followed by 42.20±1.10 man days year-1 for youths and 19.71±0.34 man days year-1 for adult male members of the family. 23.33% poultry rearers marketed their eggs directly to consumer followed by 20.00% at village market, 5.83% poultry rearers sold their eggs to the middleman and 5.00% to feriwala. Majority (41.67%) of them marketed their live birds directly to consumers followed by feriwala (22.50%), at village market (19.17%) and 13.33% poultry rearers sold their birds to the middleman. Present study concluded that in traditional backyard poultry rearing adult female and youths had more man days employment in Bastar district and most of the tribal poultry rearers market their eggs and birds directly to the consumers due to their social nature of livelihood.